A new procedure for fast soft staining of BN‐PAGEs on photosynthetic complexes. Issue 3 (22nd November 2016) - Farci, Domenica; Kirkpatrick, Joanna; Piano, Dario
Abstract : We report a fast and sensitive procedure for blue native PAGE staining, in which the conventional staining step with CBB is avoided. After running, a short exposure to a mix of polar protic solvents (ethanol and acetic acid) leads to a fast and selective removal of the dye from the migration front and a specific binding to the protein bands, while the rest undergo a selective and complete background removal, leading to an intense contrast. This single‐step staining–destaining technique is useful in protein samples that bind colored cofactors such as photosystems, which can be selectively discerned by their characteristic green color. After the staining of such samples, the green color persists, while the other unpigmented protein complexes and the molecular standard remain CBB stained, creating a useful reference system for the assignment of the bands. The advantages and chemical basis of this staining procedure are discussed.